Thailand in the Cold War - Phillips, Matthew (Routledge studies in the modern history of Asia, 2016)
Considering popular culture, including film, literature, fashion, tourism and attitudes towards Buddhism, the book shows how an ideology of consumerism and integration into a "free world" culture centred in the United States gradually took hold and became firmly established, and how this popular culture and ideology was fundamental in determining Thailand's international political alignment.